2017
DOI: 10.1021/acs.jpcb.6b11506
|View full text |Cite
|
Sign up to set email alerts
|

Pierced Lasso Topology Controls Function in Leptin

Abstract: Protein engineering is a powerful tool in drug design and therapeutics, where disulphide bridges are commonly introduced to stabilize proteins. However, these bonds also introduce covalent loops, which are often neglected. These loops may entrap the protein backbone on opposite sides, leading to a "knotted" topology, forming a so-called Pierced Lasso (PL). In this elegant system, the "knot" is held together with a single disulphide bridge where part of the polypeptide chain is threaded through. The size and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…It has been proposed that knotted proteins have enhanced thermal (20,26), mechanical (26,27,128) and structural (127) stabilities. Another possibility is that knots help shape and stabilize the active site of enzyme (129)(130)(131), and in some cases it has even been suggested that knots can control enzymatic (130) and signaling activity (132). A recent study put forward the view that knots can impair protein degradation by ATP-dependent proteases leading to partially degraded products with potentially new functions (133).…”
Section: Functional Advantages Of Knots In Proteinsmentioning
confidence: 99%
“…It has been proposed that knotted proteins have enhanced thermal (20,26), mechanical (26,27,128) and structural (127) stabilities. Another possibility is that knots help shape and stabilize the active site of enzyme (129)(130)(131), and in some cases it has even been suggested that knots can control enzymatic (130) and signaling activity (132). A recent study put forward the view that knots can impair protein degradation by ATP-dependent proteases leading to partially degraded products with potentially new functions (133).…”
Section: Functional Advantages Of Knots In Proteinsmentioning
confidence: 99%
“…To complement the picture obtained by means of the EFM we have performed a set of folding simulations employing the well-established GōM proposed by Clementi et al (26), that has already been used by Haglund et al to study lasso proteins (20,22,23). For details on the description we refer to the cited references, here we just underline that the native contacts establish through a 12-10 Lennard Jones potential, which is the main driving force of the folding.…”
Section: Gō Modelmentioning
confidence: 99%
“…Since Leptin was classified as the first CL protein(20), this topological state has been found to be widespread in the known PDB structures, characterizing about 18% of the proteins containing a cysteine bridge(21). Most of the CLs are secreted proteins, with signaling functions, and their topology is believed to have a crucial role in their biological activity (22,23). Moreover, the topology of CLs can be controlled externally, since the cysteine bridge is stable in an oxidizing solution, while it does not form in a reducing environment.…”
mentioning
confidence: 99%
See 2 more Smart Citations